Implementation of Parental Involvement in Learning Civic Education - Fitra Waluyandi; Rini Trihastuti; Moh. Muchtarom (BIRCU, 2020)
Parental involvement in learning civic education is the key to success in learning civic education. Therefore, civic education teachers have a great interest in involving parents in achieving the goals of learning civic education in their class. This study attempts to provide an alternative means of implementing parental involvement in civic education learning. This study aims to classify the roles that can be played by schools, civic education teachers and also parents. From the review of articles on parental involvement theory and models, it can be classified the roles of schools, teachers and parents applicatively.